2007
DOI: 10.1080/13803390590954182
|View full text |Cite
|
Sign up to set email alerts
|

Amnesia and driving

Abstract: Two experienced drivers who developed severe amnesia due to bilateral hippocampal lesions participated in a series of standardized challenges of driving performance and knowledge of driving rules. During drives in a high fidelity simulator and on the road in an instrumented vehicle, they demonstrated vehicle control similar to that of normal drivers on measures of steering, speed control, safety errors, and driving with distraction. Their knowledge of driving rules, safety procedures, and road sign meaning als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Furthermore, the presence of memory impairments may interact with impairments in other cognitive domains relevant to driving. To isolate the effects of memory impairment in driving, Anderson et al (2007) found that drivers with severe amnesia due to bilateral hippocampal lesions were not impaired in most aspects of driving performance (knowledge of driving rules, safety procedures, and road sign meaning were normal), but presented some difficulties in following route directions on the road. A study from Grace et al (2005) that compared neuropsychological and driving performance in AD and Parkinson Disease patients found that severe memory impairment in the AD group (i.e., a cortical dementia with impaired learning, retrieval and recognition memory) did not relate to poor driving, but memory impairment in the unsafe Parkinson disease group (i.e., a subcortical dementia with impaired retrieval but relatively preserved recognition) reflected the influence of executive dysfunction on memory.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of memory impairments may interact with impairments in other cognitive domains relevant to driving. To isolate the effects of memory impairment in driving, Anderson et al (2007) found that drivers with severe amnesia due to bilateral hippocampal lesions were not impaired in most aspects of driving performance (knowledge of driving rules, safety procedures, and road sign meaning were normal), but presented some difficulties in following route directions on the road. A study from Grace et al (2005) that compared neuropsychological and driving performance in AD and Parkinson Disease patients found that severe memory impairment in the AD group (i.e., a cortical dementia with impaired learning, retrieval and recognition memory) did not relate to poor driving, but memory impairment in the unsafe Parkinson disease group (i.e., a subcortical dementia with impaired retrieval but relatively preserved recognition) reflected the influence of executive dysfunction on memory.…”
Section: Discussionmentioning
confidence: 99%
“…However, driving during these evaluations may not provide a representative sample of a person's typical driving behavior, and there are limitations including practicality and expense, particularly if repeated assessment is needed to monitor possible changes in driving safety status (Brown & Ott, 2004). Performances on tests of driver knowledge, such as State licensing exams, may not reflect the person's application of that knowledge while driving, and also may be preserved even in the face of substantial acquired cognitive deficits, such as dense amnesia (e.g., Anderson et al, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The relationship of hippocampal volumes to driving ratings likely is not directly linked to the strong association of the hippocampus with declarative memory and amnesia 34 , as these neurocognitive processes are not central to deficits in driving performance 9,35 . Although memory impairment was associated with poor driving in a meta-analytic study of dementia patients, visuospatial skills were found to be more important 36 .…”
Section: Discussionmentioning
confidence: 99%